Integrative genomic analysis of ghost cell odontogenic carcinoma. Issue 9 (September 2015) - Bose, Pinaki; Pleasance, Erin D.; Jones, Martin; Shen, Yaoqing; Ch'ng, Carolyn; Reisle, Caralyn; Schein, Jacqueline E.; Mungall, Andrew J.; Moore, Richard; Ma, Yussanne; Sheffield, Brandon S.; Thomson, Thomas; et al.
Highlights First whole genome and transcriptome profiling of ghost cell odontogenic carcinoma. Mutations were detected in novel and known cancer genes. Expression profiling shows that GCOC is distinct from previously sequenced cancers. Therapeutic recommendations were made based on integrative pathway analysis.